Peranan Kompos Sampah Pasar Dengan Bioaktivator Mol Dan Trichoderma Terhadap Peningkatan Sifat Biologi Tanah Bekas Tambang Batubara - Roro Kesumaningwati; Nurul Puspita Palupi (Agrifarm : Jurnal Ilmu Pertanian, 2018)
The former coal mines experienced biological changes that caused biodiversity loss compared to natural ecosystems. Habitats decline dramatically when changes from natural ecosystems to open land occur. The frequency of land processing due to land reclamation activities has a major impact on soil organisms. Coal mining activities result in a decrease in the population of microorganisms and the activity of soil fauna, mainly due to changes in soil temperature, humidity, and the amount and quality of organic matter. This research was conducted for 1 (one) fiscal year. This research includes the making of microorganism solutions, Trichoderma enrichment, composting from market waste with bioactivator moles and trichoderma, incubating ex-coal mine land by utilizing compost, and analyzing the total population of soil microorganisms. The results showed that 1. There was an increase in the population of microorganisms in the soil that were applied to market waste compost, 2. Mushrooms found on ex-coal mine land that were applied with market waste compost with Trichoderma bioactivator, and banana weed MOL were: Aspergillus, Trichoderma, Fusarium, Mucor, Phytium, and Gliocladium, while the bacteria found were basil gram (-) Azotobacteraceae and cocci gram (-) Azotobacteraceae.